ASME 3rd International Conference on Microchannels and Minichannels, Part B Cont’d 2005
DOI: 10.1115/icmm2005-75122
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State and Transient Performance of a Miniature Loop Heat Pipe

Abstract: A series of tests have been carried out with a miniature loop heat pipe (mLHP), which has been developed for consumer electronics cooling, for horizontal and four vertical orientations under different sink temperatures. The mLHP has a cylindrical evaporator of 5 mm outer diameter and 29 mm length. The steady-state operating characteristics are similar for different orientations except for the orientation where the evaporator is above the compensation chamber. At an evaporator temperature of 75 °C, an evaporato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Water, ammonia, acetone, propane and toluene are usually used as working fluids. The temperature difference between evaporator and heat sink increases with heat flow rate, Q, whereas the total thermal resistance decreases with Q [2,[8][9][10]. Thermal performance of a heat pipe, expressed by high values of Q, is improved at large values of diameter and inclination angle as well as at low values of length and wall thickness [8,11].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Water, ammonia, acetone, propane and toluene are usually used as working fluids. The temperature difference between evaporator and heat sink increases with heat flow rate, Q, whereas the total thermal resistance decreases with Q [2,[8][9][10]. Thermal performance of a heat pipe, expressed by high values of Q, is improved at large values of diameter and inclination angle as well as at low values of length and wall thickness [8,11].…”
Section: Introductionmentioning
confidence: 89%
“…It is defined as the temperature difference between the evaporator and the heat sink divided by the dissipated heat flow rate, Q. The total thermal resistance is a function of a large number of variables, such as heat pipe geometry and material, wick structure, working fluid properties, evaporator and condenser length [2,4,[8][9][10][11]. There are several types of wick structures, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was able to predict the decreasing length of the condenser two-phase zone under the constant conductance mode caused by the volume expansion of the liquid in the compensation chamber, and was in good agreement with the experimental data. A series of tests have been carried out by Chen et al [7] with a miniature loop heat pipe (mLHP), which was developed for consumer electronics cooling with four horizontal and four vertical orientations under different sink temperatures. The mLHP was a cylindrical evaporator of 5 mm outer diameter and 29 mm length.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there have been quite a few literatures that reported the operation characteristics of LHPs on the ground, which showed their capability of transporting heat over a long distance under antigravity conditions and revealed their transient startup and power cycling characteristics [21][22][23][24]. It has been found that the relative orientation of the components has significant effect on the startup and steady-state performance of LHPs under terrestrial surroundings, which is briefly reviewed here.…”
Section: Introductionmentioning
confidence: 99%